Numerical simulations for swirlmeter on flow fields and metrological performance. (February 2018) - Chen, Desheng; Cui, Baoling; Zhu, Zuchao
Measurements of flow rates of fluids are important in industrial applications. Swirlmeters (vortex precession meters) are widely used in the natural gas industry because of their advantage in having a large measurement range and strong output signal. In this study, using air as a working medium, computational fluid dynamics (CFD) simulations of a swirlmeter were conducted using the Reynolds-averaged Navier–Stokes (RANS) and renormalization group (RNG) k–ε turbulence models. The internal flow characteristics and the influence of the tube structure (geometric parameter of flow passage) on metrological performance were studied, with a particular focus on the meter factor. Calibration experiments were performed to validate the CFD predictions; the results show good agreement with those from simulations. From the streamline distributions, a clear vortex precession is found in the throat region. At the end of throat, the pressure fluctuation reached a maximum accompanied by the largest shift in the vortex core from the centreline. There exists a large reverse flow zone in the vortex core region in the convergent section. To mitigate the influence of reverse flow on vortex precession, a suitable length of throat is required. For a larger convergent angle, the fluid undergoes higher acceleration leading to an increase in velocity that produces more intensive pressure fluctuations. The minor diameter of the throat also produces a higher velocity and larger meter factor. Compared with both divergent angle and throat length, the convergent angle and throat diameter play a more important role in determining precession frequency.